Donor‐Acceptor Type π‐Conjugated Copolymers Based on Soluble Benzodifuranone. Issue 1 (December 2014) - Kimoto, Atsushi; Tajima, Yusuke; Lendlein, Andreas; Domb, Abraham J.
Summary We designed a soluble building block containing a backbone based on benzodifuranone (BDF), a high‐performance pigment, to form a novel donor‐acceptor type polymer. By attaching dodecylthienyl moiety to the less soluble BDF framework, the soluble BDF monomer was readily obtained and applied to Suzuki‐Miyaura condensation with electron‐rich carbazole moiety to form a new class of low‐bandgap polymers. The structural characterization and estimation of the molecular weight of the target π‐conjugated polymer (PCTBDF) was carried out by 1H NMR spectroscopy and gel permeation chromatography. We determined its optical and electrochemical properties, investigating how they were affected by different molecular weights. The HOMO and LUMO energy levels were estimated to be typically –5.5 and –3.8 eV, respectively.